The Use of Literary Works in English Language Teaching - Indah Wiwik Lestari; Hafsa Namhar (Journal of English Language Teaching and Literature, 2020)
The low self-confidence in speaking can impede language acquisition. The purpose of this study was to prove and evaluate the effects of using drama for English Language Learners. It was hypothesized that drama would be helpful in lowering the affective filter psychological attributes. In addition, it can improve students’ self confidence. A group of students who had good comprehension of English, yet, were reluctant to speak. Drama was successful in considerably reducing the students participants’ anxiety and increasing their confidence and motivation towards speaking English.